Composition and bioaccessibility of elements in green seaweeds from fish pond aquaculture. (March 2018) - Afonso, C.; Cardoso, C.; Ripol, A.; Varela, J.; Quental-Ferreira, H.; Pousão-Ferreira, P.; Ventura, M.S.; Delgado, I.M.; Coelho, I.; Castanheira, I.; Bandarra, N.M.
Abstract: The elemental composition of five species of green seaweeds ( Chaetomorpha linum, Rhizoclonium riparium, Ulva intestinalis, Ulva lactuca, Ulva prolifera ) grown in fish pond aquaculture systems were studied. The elemental bioaccessibility in these species was also investigated through the application of an innovative in vitro digestive model of the human gastrointestinal tract. It was observed that R. riparium had the highest levels of Mn, Sr, Cd, Sn, and I and that U. lactuca had the highest Ni and Cu concentrations. The daily amounts of dried green seaweed required for achieving specific dietary intakes were calculated, namely: 7 g of dried U. lactuca (for meeting Cu Recommended Daily Allowance, RDA); 173 g of dried U. lactuca (Zn RDA); 78 g of dried C. linum (Se RDA); 41 g of dried C. linum (Mo RDA); and 0.5 g of dried R. riparium (I Dietary Reference Intake, DRI). Concerning elemental bioaccessibility, Mn and Cu had the highest values, always above 50%, I values were in the lower range, between 14 and 31%. The elemental bioaccessibility range of R. riparium (31–100%) was higher than the ranges for other species, particularly C. linum (0–56%). The bioaccessibility results entailed higher quantities of dried seaweed for reaching dietary intakes: 10 g of dried U. lactuca (Cu RDA); 290 g of dried R. riparium (Zn RDA); and 2 g of dried R. riparium (I DRI). Accordingly, R. riparium is a very rich I source. This study showed the importance of taking into account bioaccessibility results in estimating dietary intakes. Graphical abstract: Highlights: Mn, Sr, Cd, Sn, & I levels were highest in R. riparium & Ni & Cu levels in U. lactuca. While Mn & Cu bioaccessibility was above 50%, I values were in the 14–31% range. Bioaccessibility entailed higher amounts of dried seaweed for meeting advised intakes. R. riparium is a very rich I source with 2 g of dried R. riparium for reaching I DRI.